Aderência concreto-concreto e aço-concreto em recuperação de estruturas de concreto armado - Doria, Mariana Rezende (2014)
In inspections of buildings, it is increasingly common to come across buildings and infrastructure works, long before they reach their useful life, are already in need of repair and reinforcement, or collapsing. This study examined the bond between concrete of different ages and between steel and concrete. Three types of treatment interface between the concrete of different ages were compared by evaluating bond. It was also evaluated the bond between steel and concrete, when the bar was inserted into the fresh concrete and when it was inserted by drilling and bond of epoxy bridge. Still, we analyzed the influence of adhesion between concrete on flexural strength. Two concrete mixtures, one for the substrate (older) and then recovery (age) measured for fck 30 MPa and 35 MPa, respectively, were measured. The bond between the two types of concrete was measured using tests that forced the interface tensile stresses, oblique shear and vertical shear. Flexural strength of the specimens constituted of two types of concrete bridges with mortar and epoxy adhesion was measured. The specimens, partially composed of concrete substrate were cured and left to air for a few months. Subsequently, received three different surface treatments: brushing, brushing or equal to that of mortar concrete substrate and brushing and epoxy layer. They were then supplemented with concrete recovery subjected to curing by immersion in water and tested. For the analysis of bond between steel and concrete, the pullout test was performed from the inserted bars in concrete. When comparing the results of tests of adherence of specimens received only brushing whose interfaces with the interfaces of the specimens that received besides brushing, layer of mortar and epoxy bridge, there was an increase in bond strength, respectively, 15% and 37 % for the adhesion test by indirect tensile, 4% and 12 % for the adherence test by oblique shear and 108% and 178 % for the vertical shear test. For the bending test, there was an increase of 41 % in modulus of rupture, when comparing the results of the test piece which received brushing and epoxy layer which received brushing and mortar layer. When were related values of the specimens of the pullout test (Pull out) who had the steel rod inserted in the concrete in the hardened state with epoxy adhesion bridge with those who had the steel rod inserted in the concrete still fresh , not observed significant loss (about 0.52 %).